Design and Consequences of CFC and GILTI Rules: A Review and Potential Lessons for the Global Minimum Tax - Michael Overesch; Dirk Schindler; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2024)
This chapter provides a description of one of the key anti-tax-avoidance rules to combat profit shifting by multinational corporations, so called Controlled Foreign Corporation (CFC) rules that directly target income in low-tax countries. We explain some key institutional features of CFC provisions. We then present some data and descriptive statistics before we review existing theoretical and empirical research analyzing CFC rules. Our review also includes the new U.S. GILTI rules. CFC rules are effective in curbing profit shifting, but their effect on the real economy is still unclear. In contrast, GILTI seems to be ineffective when it comes to profit shifting, but it has consequences for real activity. We finally argue that research on CFC regulations and GILTI can be informative in assessing the recent global minimum tax initiative.
Keywords: H25; F23; 330; Controlled-foreign-company (CFC) Rules; Global Intangible Low-taxed Income (GILTI); tax havens; tax avoidance; effects of regulation; global minimum tax